Microencapsulation of Zidovudine Using Colophony: Confirming Natural Resin as Microparticulate Drug Carrier - Satyajit Panda; Snigdha Pattnaik; Laxmidhar Maharana (Technological Innovation in Pharmaceutical Research Vol. 5, 2021)
The aim of the present study was to develop and evaluate natural biodegradable microcapsules of zidovudine (AZT) by using colophony resin as microencapsulating agent. An industrially feasible emulsification-solvent evaporation method was used for preparation of different batches of microcapsules. The proposed system was evaluated in vitro for particle morphology, microencapsulation efficiency, production yield, micromeritic properties, release profile and release kinetics etc. Physico-chemical characteristics of AZT and AZT loaded microcapsules were evaluated by differential scanning calorimetry (DSC), X-ray diffraction (XRD), and infrared spectroscopy (FTIR). The resin coated microcapsules were found to be spherical, discrete and free flowing. Microencapsulation efficiency was in a narrow range (91-97%) suggesting an identical distribution of drug in different batches. DSC and XRD results showed a partial modification in AZT’s solid state. Zidovudine release from optimized batches of resin coated microcapsules was slow and over 24 hours depending on the core: coat ratio. Drug release was found to be following Fickian diffusion mechanism. Wall thickness was found to be increasing with the increase in the resin concentration. The t50% values of various formulated batches were found to be increasing with corresponding decrease in the permeability constant values. The resin coated microcapsules exhibited good controlled release characteristics and were found to be suitable for once a day oral controlled release product.